1990
DOI: 10.1007/bf02336592
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic treatment of cholelithiasis

Abstract: Surgical management of gallstones was first performed successfully in 1878. Over the past decade, several new treatment alternatives have evolved that challenge the supremacy of traditional surgical cholecystectomy. Two endoscopic alternatives, e.g., percutaneous cholecystolithotomy (PCCL) and laparoscopic cholecystectomy (LC) are the latest additions to the growing armamentarium. Our initial experience with PCCL and LC as compared with our traditional cholecystectomy experience shows a 57% reduction in hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that the postoperative pain as well as the duration of hospital stay are significantly reduced after minimal access surgery compared to conventional procedures. Laparoscopic cholecystectomy has resulted in a reduction of hospital days of 58% and a reduction of postoperative anal gesic dose of 57% [6], Although the role of laparoscopic surgery is well established in benign disease, there is ongoing controversy on the application of this technique in oncology. While diagnostic laparoscopy is a generally accepted method for staging of intraabdominal malignancies, there is only limited experience with minimal access surgery.…”
Section: Laparoscopymentioning
confidence: 99%
“…It has been demonstrated that the postoperative pain as well as the duration of hospital stay are significantly reduced after minimal access surgery compared to conventional procedures. Laparoscopic cholecystectomy has resulted in a reduction of hospital days of 58% and a reduction of postoperative anal gesic dose of 57% [6], Although the role of laparoscopic surgery is well established in benign disease, there is ongoing controversy on the application of this technique in oncology. While diagnostic laparoscopy is a generally accepted method for staging of intraabdominal malignancies, there is only limited experience with minimal access surgery.…”
Section: Laparoscopymentioning
confidence: 99%